On Their Own Terms: How Cocalera Organizing Expanded Indigenous Women’s Rights in Bolivia - Linda Farthing; Thomas Grisaffi (Latin American Research Review, 2024)
A key element in the historically unprecedented advances in indigenous women’s political representation under Bolivia’s Evo Morales’s administration (2006–2019) was the influence that women coca growers played in the rural women’s indigenous organization known as the Bartolinas. Driven in no small measure by their resistance to the US-financed War on Drugs in the Chapare region, the cocaleras became both Bolivia’s strongest indigenous women’s organization and its most dedicated advocates for indigenous women’s rights. This article contends that intersectionality—of gender, class, and indigenous identities—is at the heart of understanding indigenous women’s transformation from “helpers” of a male-dominated peasant union to government ministers in the space of ten years. Not only did they effectively deploy chachawarmi, the Andean concept of gender complementarity, to advance their rights in a way consistent with their cultural identity and political loyalties, but they also benefited from the gains of a predominantly urban middle-class feminist movement even though they formally rejected the feminist movement’s composition and perceived orientation.